ANALISIS PENYEBAB ANAK PUTUS SEKOLAH (STUDI DI DESA LANTAGI KECAMATAN KULISUSU KABUPATEN BUTON UTARA) - Ibrahim Ibrahim; M Ridwan Said Ahmad; Andi Dody May Putra Agustang; Andi Sadriani (Social Landscape Journal, 2024)
This research aims to analyze the causes of children dropping out of school in Lantagi Village, Kulisusu District, North Buton Regency. The phenomenon of children dropping out of school is a common phenomenon that often occurs in both urban and rural communities. This research uses symbolic interaction theory from Hebert Blumer to examine more deeply the phenomenon of children dropping out of school. This research uses descriptive qualitative research methods. Data collection techniques in this research used observation, interview and documentation techniques. The research location is located in Lantagi Village, Kulisusu District, North Buton Regency. The data collection technique in this research used a purposive sampling technique with 12 informants. The data analysis technique in this research uses data reduction techniques, data presentation and drawing conclusions. The data validation technique in this research uses the Member Check technique, which is a data collection technique by re-interviewing informants so that it is said to be valid. The results of the research show that the cause of children dropping out of school in Lantagi Village, Kulisusu District, North Buton Regency is caused by several factors, namely economic factors, family factors, internal desire factors and children's mindset about school.